MicroRNA-34a regulates the longevity-associated protein SIRT1 in coronary artery disease: effect of statins on SIRT1 and microRNA-34a expression - Tabuchi, Tsuyoshi; Satoh, Mamoru; Itoh, Tomonori; Nakamura, Motoyuki (Clinical science (1979), 2012)
Endothelial senescence is thought to play a role in CAD (coronary artery disease). miR-34a (microRNA-34a) and other SIRT1 (silent information regulator 1)-related miRs have recently been found to target SIRT1 leading to endothelial senescence. In the present study, we investigated whether SIRT1-related miRs, including miR-9, miR-34a, miR-132, miR-181a, miR-195, miR-199a, miR-199b and miR-204, and SIRT1 were expressed in EPCs (endothelial progenitor cells) obtained from patients with CAD, and whether statins (atorvastatin or rosuvastatin) affected these levels. To determine the effects of miR-34a on SIRT1, cultured EPCs transfected with miR-34a were analysed for total SIRT1 protein levels. EPCs were obtained from 70 patients with CAD and 48 subjects without CAD. Patients with CAD were randomized to 8 months of treatment with atorvastatin or rosuvastatin. EPCs were obtained from peripheral blood at baseline and after 8 months of statin therapy. Levels of miRs and SIRT1 in EPCs were measured by real-time RT–PCR (reverse transcription–PCR) and FACS. Functional approaches to miR-34a have shown that transfection of miR-34a into EPCs resulted in regulation of SIRT1 expression. Levels of miR-34a were higher in the CAD group than in the non-CAD group, whereas levels of SIRT1 protein were lower in the CAD group than in the non-CAD group. There were no significant differences in other miRs (miR-9, miR-132, miR-181a, miR-195, miR-199a, miR-199b and miR-204) between the two groups. Levels of miR-34a were mildly negatively correlated with SIRT1 protein levels. A randomized clinical study has shown that the atorvastatin group had markedly decreased miR-34a levels and increased SIRT1 levels, whereas the rosuvastatin group showed no change in these levels. Levels of other miRs remained unchanged in the atorvastatin and rosuvastatin groups. In conclusion the results of the present study suggest that miR-34a may regulate SIRT1 expression in EPCs and that atorvastatin up-regulates SIRT1 expression via inhibition of miR-34a, possibly contributing to the beneficial effects of atorvastatin on endothelial function in CAD.